An Experimental Analysis of In-Group Favoritism and Out-Group Discrimination in the Gain and Loss Domain - Armenak Antinyan; Tigran Aydinyan; Anna Ressi; Lilia Wasserka-Zhurakhovska (Center for Economic Studies and ifo Institute (CESifo), 2023)
While the existence of the in-group bias is a well-researched phenomenon in Economics, the established findings are of limited value for understanding its dynamics in the context of challenging societal and economic times. The aim of this paper is to shed more light on whether intergroup discrimination manifests itself differently in a loss compared to a gain domain (corresponding to periods of economic upturns and downturns). We run an online experiment with natural identities, in which participants allocate money between three recipients who vary in the social distance to the decision-maker. We find that, on average, the in-group favoritism documented in the gain domain vanishes in the loss domain. While this result seems to imply that participants become egalitarian in the loss domain, it is actually driven by out-group favoring allocation types becoming more extreme in their decisions. Overall, the loss domain leads to a stronger polarization regarding the question of how different social groups in the society should be treated.
Keywords: C99; D30; D63; D91; J10; J15; 330; in-group bias; favoritism; discrimination; gain and loss domain; polarization